2015
DOI: 10.1093/cesifo/ifv014
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Term Employment and Fertility: Evidence from German Micro Data

Abstract: This series presents research findings based either directly on data from the German Socio-Economic Panel Study (SOEP) or using SOEP data as part of an internationally comparable data set (e.g. CNEF, ECHP, LIS, LWS, CHER/PACO). SOEP is a truly multidisciplinary household panel study covering a wide range of social and behavioral sciences:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…A body of empirical work has uncovered a negative correlation between fertility and aggregate measures that arguably reflect insecurity: the OECD country-level unemployment rate, unemployment benefits and maternity benefits in Adsera (2004); country-level unemployment rates and production volatility in Hondroyiannis (2010); the US State unemployment rate in Schneider (2015); the regional unemployment and redundancy rates after the fall of the Berlin Wall in Chevalier and Marie (2017); and the State-cohort volatility of income growth in Chabé-Ferret and Gobbi (2018). ECINEQ WP 2020-532 May 2020 At the individual level, fertility has also been shown to fall with subjective measures of insecurity (perceived job security in Scherer, 2009, and worries about own economic situation in Kreyenfeld, 2015) as well as objective individual measures of insecurity such as persistent joblessness in Busetta et al (2019) and being on a fixed-term contract in Adsera (2004), De la Rica and Iza (2005), Kind and Kleibrink (2013), Modena et al (2014), Auer and Danzer (2016), Guner et al (2019) and Lopes (2020).…”
Section: Introductionmentioning
confidence: 99%
“…A body of empirical work has uncovered a negative correlation between fertility and aggregate measures that arguably reflect insecurity: the OECD country-level unemployment rate, unemployment benefits and maternity benefits in Adsera (2004); country-level unemployment rates and production volatility in Hondroyiannis (2010); the US State unemployment rate in Schneider (2015); the regional unemployment and redundancy rates after the fall of the Berlin Wall in Chevalier and Marie (2017); and the State-cohort volatility of income growth in Chabé-Ferret and Gobbi (2018). ECINEQ WP 2020-532 May 2020 At the individual level, fertility has also been shown to fall with subjective measures of insecurity (perceived job security in Scherer, 2009, and worries about own economic situation in Kreyenfeld, 2015) as well as objective individual measures of insecurity such as persistent joblessness in Busetta et al (2019) and being on a fixed-term contract in Adsera (2004), De la Rica and Iza (2005), Kind and Kleibrink (2013), Modena et al (2014), Auer and Danzer (2016), Guner et al (2019) and Lopes (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies examined the consequences of fixed-term employment on entering parenthood. Some studies for Germany showed that the transition to parenthood was significantly delayed in those partnerships where at least one of the two partners worked under a fixed-term contract (Auer/Danzer 2016;Düntgen/Diewald 2008;Kind/Kleibrink 2013;Kreyenfeld 2008). Additionally, Laß (2017: 182) found a prolonging effect for women who worked under a fixed-term part time contract.…”
Section: Previous Researchmentioning
confidence: 99%
“…But it is still an open question to what extent fixed-term employment affects the realization of important partnership events. While some studies found evidence for a significant delay of important partnership events, such as entering parenthood (Auer/Danzer 2016;Düntgen/ Diewald 2008;Kind/Kleibrink 2013;Kreyenfeld 2008), other research did not find significant associations between fixed-term employment and the transition to parenthood (Brose 2008;Gebel/Giesecke 2009;Kreyenfeld 2010;Kurz et al 2005;Schmitt 2012b;Tölke/Diewald 2003). However, previous research on the impact of fixed-term employment on important partnership events is mostly limited to family formation.…”
Section: Introductionmentioning
confidence: 99%
“…This average hides considerable variation; ranging from a share below three per cent in the Baltic States and Romania to over 25 per cent in Spain. Fixedterm contracts have long-term negative impacts on wages (Pavlopoulos, 2013;Yoon and Chung, 2016) and are associated with delayed childbirth and worse mental health (Auer and Danzer, 2016;Scheuring, 2020). Contract type is also related to attitudes; people on fixed-term contracts are more in favor of income redistribution and political parties that support these policies (Marx and Picot, 2013;Marx, 2014;Vlandas, 2020).…”
Section: Fixed-term Contracts As a Labor Market Insecuritymentioning
confidence: 99%